Comparative signal-to-noise analysis of fibre-optic based optical coherence tomography systems - Ford, Helen D.; Beddows, R.; Casaubieilh, P.; Tatam, Ralph P. (Taylor & Francis, 2005)
Several optical coherence tomography ( OCT) systems are proposed using optical. fibre components and based around Fizeau sensing interferometers. The theoretical signal- to- noise ratio ( SNR) is calculated for each of the proposed configurations, using a constant set of assumed values for illumination and detection parameters. The SNR values obtained are compared with values calculated for typical existing configurations based around Michelson interferometers. Fizeau- based systems incorporating a secondary processing interferometer offer the advantage over current interferometer configurations of down- lead insensitivity, which prevents signal fading and reduces thermal fringe drift. The most basic form of the Fizeau system makes inefficient use of optical power, and has a low SNR compared with the widely used Michelson configuration. However, the results of the analysis described in this paper show that the SNR for more sophisticated Fizeau configurations, incorporating optical circulators and balanced detection systems, can be as high as the value for the most sensitive existing fibre- based OCT systems. Fizeau configurations therefore offer the combined advantages of optimized SNR and down- lead insensitivity, indicating their suitability for use in relatively poorly controlled environments such as in- vivo measurements.
Keywords: OCT, Optical coherence tomography